Celebrity in death - Robb, J. D., 1950- (New York : G.P. Putnam's Sons, 2012)
NYC Lt. Eve Dallas investigates the death of a young actress with the assistance of her husband Rourke and Detective Peabody.
English language and literature.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Actresses -- Crimes against -- Fiction; Husband and wife -- Fiction; Celebrities -- Fiction; Policewomen -- Fiction; Women detectives -- Fiction; Police -- New York (State) -- New York -- Fiction; Women detectives -- New York (State) -- New York -- Fiction; Motion picture industry -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction